2020
DOI: 10.2196/16063
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Work-Hours Recorder for Medical Staff (Staff Hours): Mobile App Development

Abstract: Background There are numerous mobile apps for tracking work hours, but only a few of them record work hours automatically instead of relying on manual logging. No apps have been customized for medical staff, whose work schedules are highly complicated as they have both regular hours and on-call duties. Objective The specific aims of this study were to (1) identify the Staff Hours app users’ GPS-defined work hours, (2) examine the overtime work hours fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In Singapore, it was implemented on interns of internal medicine department [6]. The study showed that even though physicians have longer total work hours than non-health care providers they even exceed those o cial schedule hours [12]. We conducted our study in Riyadh, Saudi Arabia among pediatrics residents to evaluate the impact of the NF system and the traditional 24-hour on-call system on several aspects.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In Singapore, it was implemented on interns of internal medicine department [6]. The study showed that even though physicians have longer total work hours than non-health care providers they even exceed those o cial schedule hours [12]. We conducted our study in Riyadh, Saudi Arabia among pediatrics residents to evaluate the impact of the NF system and the traditional 24-hour on-call system on several aspects.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…However, most of them require users to manually clock in and out due to the apps’ lack of an automatic geofencing feature. Chiang et al overcame this fundamental limitation by designing “Staff Hours”, an app that automatically chronicles users’ work patterns via a highly accurate, yet power-saving, GPS-defined algorithm [ 30 ]. Being the first of its kind, “Staff Hours” was specifically designed to monitor overwork patterns and occupational burnouts among medical staffs.…”
Section: The Application Of Mobile Technologies In Mental Health Rese...mentioning
confidence: 99%
“…Using aggregated datasets collected by “Staff Hours”, researchers can compare work hours between different types of healthcare personnel, as well as among workers of vastly disparate occupations. Figure 5 shows that medical staff had longer work hours than nonhealthcare professionals, and resident physicians worked longer hours than visiting staff in hospitals [ 30 ]. With the inclusion of regulations pertaining to resident physicians’ work hour limits in Taiwan’s Labor Standards Act in September 2019, this app took on another purpose in labor negotiations, serving as a real-time monitor for work hour limit compliance and evidence for employees when they claim overtime pay.…”
Section: The Application Of Mobile Technologies In Mental Health Rese...mentioning
confidence: 99%
“…Staff Hours is a newly designed app that captures the work hours and patterns of medical staff in real time [11]. Participants installed the Staff Hours app onto their smartphones from Apple's App Store or Android's Google Play store.…”
Section: Gps-defined Work Hours Recorded By the Appmentioning
confidence: 99%
“…Currently, the widespread use and deep reach of smartphones in modern life enable the measurement of work hours in an affordable, reliable, and unobtrusive way. We developed an app, "Staff Hours," to automatically calculate a user's work hours via GPS background data [11]. Staff Hours is a region-restricted app, which could only be downloaded in Taiwan.…”
Section: Introductionmentioning
confidence: 99%